2003
DOI: 10.1373/clinchem.2003.021725
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Approach to Immunosuppressive Therapies Using Calcineurin Inhibitors and Mycophenolate Mofetil

Abstract: Background: Graft survival depends on adequate immunosuppression. To evaluate the effect on the immune system of immunosuppressive therapies using calcineurin inhibitors (CNIs), several pharmacodynamic indices have been proposed to complement pharmacokinetic data. In this preliminary study we compared some of these parameters during combined immunosuppressant therapies. Methods: We treated 65 stable renal transplant recipients with cyclosporin A (CsA; n ‫؍‬ 16), tacrolimus (TRL; n ‫؍‬ 10); CsA ؉ mycophenolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…MMF can selectively suppress the proliferation of lymphocytes, decrease the formation of antibodies, 27 and exhibit multifarious effects on endothelial cells. 28 In addition, Millan et al 29 found that MMF can suppress IL-2 production additionally when given with tacrolimus. Thus, a combined therapy with MMF, tacrolimus, and steroids was supposed to act on inflammatory, proliferative, vasculitic, and membranous le- sions synchronously.…”
Section: Discussionmentioning
confidence: 99%
“…MMF can selectively suppress the proliferation of lymphocytes, decrease the formation of antibodies, 27 and exhibit multifarious effects on endothelial cells. 28 In addition, Millan et al 29 found that MMF can suppress IL-2 production additionally when given with tacrolimus. Thus, a combined therapy with MMF, tacrolimus, and steroids was supposed to act on inflammatory, proliferative, vasculitic, and membranous le- sions synchronously.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that PBMC-sensitivity towards in regard to a number of drugs could be tested before a renal transplantation was carried out, and the patient could be treated with the drug to which they displayed the most sensitivity [7,41]. The measurement of calcineurin activity [43], IL-2 amount produced from PBMCs [21,44], or the amount of IL-2 mRNA in PBMCs [21,45] instead of examining blastogenesis-inhibition by the drug may be of help for the evaluation of the immunosuppressive efficacy of calcineurin inhibitors in renal transplantation.…”
Section: Organ Transplantationmentioning
confidence: 99%
“…Cellular pharmacodynamic approaches using PBMCs for the evaluation of clinical mycophenolate mofetil efficacies has been applied [21,28,51]. Measuring inosine-monophosphate dehydrogenase activity in PBMCs [52] and IL-2 concentrations in PBMC cultures [53] as well as estimating PBMC-blastogenesis [28] would be useful for the tailored-therapy of mycophenolate mofetil in renal transplant recipients. Similar approaches for rapamycin have also been conducted [54,55].…”
Section: Organ Transplantationmentioning
confidence: 99%
“…Mycophenolic acid and steroids both affect the enzyme inosine monophosphate dehydrogenase 2 in CD4 + PBL which provides guanosine nucleotides for DNA replication of T lymphocytes after cell activation [5]. Addition of mycophenolic acid to cyclosporine or tacrolimus-based immunosuppression reduces IL-2 production [25]. Anti-CD3 antibodies deplete CD3 + PBL and block T cell activation of the remaining T PBL due to shedding of CD3 from the cell surface after CD3 antibody binding.…”
Section: Different and In Part Interfering Pharmacodynamics Of Combmentioning
confidence: 99%